Aquaculture-Related Applications of DNA Microarray Technology - Matthew L. Rise; Zhanjiang Liu; Susan E. Douglas; Laura L. Brown; John H.E. Nash; Margaret J. McFall-Ngai (Blackwell Publishing, 2025)
DNA microarrays printed on glass slides have been available for some aquaculturerelevant species since 2004, and global gene expression studies involving new aquatic animal DNA microarray platforms are appearing in the literature virtually every month. In a very short time, DNA microarrays have become popular tools for aquaculture-related research. This is not surprising given that these genomic tools have recently revolutionized scientific research in other areas such as toxicology, agriculture, biomedicine, and developmental biology. There is a growing literature on the use of fish DNA microarrays for studies related to toxicology (e.g., Finne et al. 2007; Gunnarsson et al. 2007) and biomedicine (e.g., Meijer et al. 2005; Lam et al. 2006) that is beyond the scope of this chapter. We will focus on microarray-based research that is directly relevant to current aquaculture industry concerns (e.g., toward developing immune-robust and rapidly growing broodstock).